2020
DOI: 10.1111/bjh.17132
|View full text |Cite
|
Sign up to set email alerts
|

Application of the LymphGen classification tool to 928 clinically and genetically‐characterised cases of diffuse large B cell lymphoma (DLBCL)

Abstract: A Phase II study of a nonmyeloablative allogeneic stem cell transplant with peritransplant rituximab in patients with BCell lymphoid malignancies: favorably durable event-free survival in chemosensitive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 9 publications
1
49
0
Order By: Relevance
“…A further modification of the HMRN classification used the presence of MYC hotspot and NOTCH1 PEST domain mutations to identify a NOTCH1 and BCL2-MYC subgroups. 41 This modified HMRN classifier showed high concordance when cases were reclassified using the NCI LymphGen classifier (Fig 4).…”
Section: Genomic Profiling Of Dlbclmentioning
confidence: 88%
See 1 more Smart Citation
“…A further modification of the HMRN classification used the presence of MYC hotspot and NOTCH1 PEST domain mutations to identify a NOTCH1 and BCL2-MYC subgroups. 41 This modified HMRN classifier showed high concordance when cases were reclassified using the NCI LymphGen classifier (Fig 4).…”
Section: Genomic Profiling Of Dlbclmentioning
confidence: 88%
“…A recent publication applied the LymphGen classifier to cases classified in the HMRN study and showed high concordance with the original HMRN assignment. 41 Indeed, the greatest source of variability was the number of cases classified at all rather than the movement between subtypes (Fig 5B). LymphGen assigned a unique classification to 53% of cases, whereas HMRN classified 73% of cases.…”
Section: Challenges Of Implementing Molecular Subtypingmentioning
confidence: 96%
“…The classification of DLBCL has recently been transformed by the discovery of genetic subtypes based on patterns of co-occurring genetic alterations (Chapuy et al, 2018;Lacy et al, 2020;Schmitz et al, 2018;Wright et al, 2020). At least seven genetic subtypes are recognized currently and have been reproducibly identified in four large DLBCL cohorts (Runge et al, 2021;Wright et al, 2020). Importantly, the DLBCL genetic subtypes differ with respect to pathogenesis, phenotypic properties, oncogenic survival pathways, and responses to therapy (Chapuy et al, 2018;Lacy et al, 2020;Schmitz et al, 2018;Wright et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several classification methods compared to LymphGen classification have been reported using the UK-HMRN cohort data. 12 Modified HMRN classification 27 with the LymphGen classification (69%). The two-step classifier 28 is a simple algorithm and also had good sensitivity and specificity; however, the concordance rate with the Lymph-Gen classification was not satisfactory in all cases (54%).…”
Section: Discussionmentioning
confidence: 99%